Investigation of Susceptibility Levels of Culex pipiens L. (Diptera: Culicidae) Populations to Synthetic Pyrethroids in Antalya Province of Turkey - Önder Ser; Huseyin Cetin (Tehran University of Medical Sciences, 2019)
Background: Culex pipiens L. (Diptera: Culicidae) is an important vector of several pathogens. This mosquito is widely distributed throughout the world. We aimed to determine the susceptibility levels of Cx. pipiens populations to some synthetic pyrethroid insecticides in Antalya, Turkey. Methods: The immature stages of mosquitoes were collected from eight locations in Alanya, Döşemealtı, Kemer, Kumluca, and Manavgat districts of Antalya between Apr and Oct of 2017. Adult susceptibility tests were carried out according to a modified version of the Centers for Disease Control and Prevention bottle bioassay. In the tests, the World Health Organization recommended diagnostic doses; permethrin (0.75%), etofenprox (0.5%), deltamethrin (0.05%) and lambda-cyhalothrin (0.05%) were used. Results: As a result of the susceptibility tests, deltamethrin was the least effective insecticide and it caused 58.78-97.56% mortalities on Cx. pipiens populations while permethrin was the most effective substance that caused 100% mortality on all populations. While all of the tested populations were found susceptible to permethrin, and possible resistant or resistant to deltamethrin. Etofenprox and lambda-cyhalothrin led to 91.54-100% and 93.1-100% mortalities, respectively. Conclusion: The possible resistance or resistance to deltamethrin in all the areas is caused by the widespread use of this chemical against pests in agriculture and public health applications for long-term. Moreover, a concordance was found between resistance levels and the intensity of pesticide application in agriculture and public health, and organic and chemical pollution levels in the sampled habitats.